Numerical and Observational Analysis of Wave Conditions and Pilot Boarding Safety in an Expanding Port Environment - Fang, Hui-Ming; Wang, Hsing-Yu (Science and Technology: Developments and Applications Vol. 7, 2025)
Pilotage services are crucial for ensuring the safe navigation of vessels entering and leaving ports. The research examines wave distributions at the pilot station using data collected from an Acoustic Doppler Current Profiler (ADCP) station and buoy. Additionally, it evaluates the impact of planned port expansions, including the construction of a new Liquefied Natural Gas (LNG) terminal and extended breakwaters, on wave characteristics and pilot operations. Numerical simulations and observational data indicate that, despite minor variations, wave height trends at the boarding area remain relatively consistent before and after expansion. The findings suggest that the proposed modifications alter wave diffraction patterns while enhancing the predictability and safety of pilot operations by reducing uncertainties in wave measurements. These insights are particularly valuable for future port development initiatives, as they provide data-driven guidance on optimizing infrastructure design, minimizing wave-induced risks, and improving pilot boarding conditions. This study contributes to the broader understanding of marine meteorology and its implications for port safety and efficiency.